A community-based positive psychology group intervention to promote physical activity among people with metabolic syndrome: Proof of concept results to inform a pilot randomized controlled trial protocol - Rachel A. Millstein; Anne N. Thorndike; Sonia Kim; Elyse R. Park; Jeff C. Huffman (Contemporary Clinical Trials Communications, 2020)
Background: Community-based physical activity interventions can offset the burden of developing chronic diseases. Positive psychology (PP) interventions may improve health behaviors, but little is known about their effectiveness in community-based prevention settings. A multilevel PP-based intervention has never been studied in people at risk for chronic diseases. Purpose: The aim of the trial is to demonstrate feasibility, acceptability, and improve physical activity. The purpose is to describe the theory, design, and rationale of the randomized controlled trial (RCT) phase of an iteratively developed physical activity intervention for metabolic syndrome. The feasibility results of the proof-of-concept phase are presented. Methods: Participants are adult primary care patients at community health centers with metabolic syndrome and low physical activity (target n = 64). The 8-week group intervention consists of weekly physical activity goal-setting and self-monitoring, positive psychology activities, and neighborhood walks. Participants rate feasibility and acceptability of sessions. Pre-post-intervention, and 24 weeks later, participants complete accelerometers, questionnaires, and biometrics. Feasibility results: Eight participants enrolled and seven completed. The median number of group sessions attended was 7 out of 8. Average ease and usefulness of sessions were rated as 7.0 (±0.5)/10 and 8.1 (±1.0)/10, respectively, indicating feasibility and acceptability. Average pre-post physical activity increased by 2152 steps and 29.25 min of MVPA/week. Discussion: This proof-of-concept trial demonstrated high feasibility and acceptability, with increased physical activity. These positive findings suggest that the RCT phase will show high feasibility, acceptability, and initial impact on physical activity.